34.6k views
1 vote
Describe the steps you would use to solve the equation
2(4x - 5) + 11 = -63.

User Chain Ro
by
5.6k points

1 Answer

5 votes

Answer:

x = -8

Explanation:

You would solve the parenthesis first by distrubuting the two to the things inside the parenthesis:

2 times 4x and 2 times -5

Once you multiply the 2 to each of the numbers the parenthesis are no longer needed.

8x - 10 + 11 = -63

Next you would want to simplify the -10 and 11

-10 + 11 = 1

Now you have simplified the the -10 and 11 and have gotten 1

8x + 1 = -63

Now you want to subtract the one on both sides in order to get it the variable by itself.

-1 + 8x + 1 = -63 -1

The one on the left side would then cancel out and 8x would be left on the left. And for the irght side you would combine the -63 and -1 to make -64.

8x = -64

Now you have to get the variable by itself and divide by 8 on both sides to cancel the 8 on the left side out. And when you do that you should get.

x = -8

User Dzhuang
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.